Flowers in American poetry - Barr, Mary Olive (My University, 1902)
Introduction: After making a study of the principal American poets, Bryant, Longfellow, Holmes, Whittier, Lowell, and Poe, I have decided they are susceptible to the beauty of the flowers which they see around them, as well as to sounds that they hear. Altogether they mention flowers about four hundred times. They admire all varieties of flowers, but roses and lilies seem to be favorites with most of them. Perhaps one reason for all these poets being nature poets is their early surroundings. By a study of their lives we find they were raised in the country or in a small village where they had access to woodland and prairie where flowers are usually very abundant. William Cullen Bryant was distinctively a student and interpreter of nature. All her aspects and voices were familiar to him, and he reproduced these to use through his poems. In many respects his poems resemble Wordsworth’s, whom he admired greatly, but we may say the spirit is less introspective than the great English poet of nature. Bryant speaks of roses eleven times in his poems. He calls June the month of roses, and sees distinctively the red rose turning in the morning to meet the kiss of the early breezes. Spring has not really come for the poets until the roses come. To him this flower is the loveliest of all lovely things, and, although it passed away soon, it is prized by him far beyond any sculptural flower. The poet draws a picture with man and roses, comparing the sinful man to a rugged brier rose blooming in the desert amid unpleasant surroundings, and the righteous man to the pure white rose, where the bush is thick with bloom even to the top. He may draw a lesson from his picture of the good shepherd, wearing red and white roses round his temples, always guiding his flocks where the roses dwell, deathless, but always gathered once more. He not only admires the rose on the bush, but thinks they should be picked and use, for if left they only fade among the foliage and the perfume is lost on the air.
Citation: Barr, Mary Olive. Flowers in American poetry. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Poetry; Flowers; Roses; Violets; Pansies; Theses